PERAN GURU DALAM MENGATASI BULLYING DI SDN 4 PANDAN WANGI TAHUN AJARAN 2025/2026 - Isna Fitriana; Lalu Awaludin Akbar; Mukminah (STKIP Subang, 2026)
This study aims to describe the role of teachers in addressing bullying behavior at SDN 4 Pandan Wangi. The research was motivated by the prevalence of bullying cases in elementary schools, particularly in verbal and physical forms. This research employed a qualitative method with a case study approach. The subjects were fifth and sixth grade homeroom teachers and students. Data were collected through observation, interviews, and documentation. The results revealed that the types of bullying occurring at SDN 4 Pandan Wangi included physical bullying (kicking, hitting, pulling hijabs, and pushing) and verbal bullying (mocking, body shaming, and calling peers by their parents’ names). The main contributing factors were family disharmony, peer influence, and socioeconomic conditions. The impacts of bullying included victims becoming withdrawn, losing self-confidence, and avoiding social interactions. Teachers played three key roles in tackling bullying: as advisors, by giving guidance and understanding about the dangers of bullying; as role models, by demonstrating respectful behavior and speech; and as facilitators, by mediating conflicts and maintaining supervision both inside and outside the classroom. However, the facilitator role was not fully optimal due to limited supervision and a lack of close teacher-student relationships.